Relapsed perinatal neuroblastoma after expectant observation. Issue 1 (30th August 2014) - Salloum, Ralph; Garrison, Aaron; von Allmen, Daniel; Sheridan, Rachel; Towbin, Alexander J.; Adams, Denise; Weiss, Brian
<x xml:space="preserve">Abstract</x> The Children's Oncology Group (COG) study ANBL00P2 showed that expectant observation of patients younger than six months of age with perinatal neuroblastoma presenting as a small adrenal mass yields excellent overall survival and spares surgical resection to the majority of patients. We report a 5‐year‐old female who was initially diagnosed with a perinatal neuroblastoma. The patient was observed on COG study ANBL00P2. By nine months of age she had no ultrasonographic or biochemical evidence of disease. She presented four years later with abdominal pain and was found to have high‐risk stage 4 MYCN amplified neuroblastoma. Pediatr Blood Cancer 2015;62:160–162. © 2014 Wiley Periodicals, Inc.